Social Medias and Sociability in The Late Modernity - Fontes, Breno Augusto Souto (Latitude, 2022)
This brief essay aims to rescue part of the very diverse research agendas, oriented from the thematic trajectories “social medias” and “sociability”. These trajectories illustrate quite clearly the importance of this theoretical-methodological framework for the investigation of a wide range of issues in the contemporary social sciences. We are particularly interested in the construction of sociabilities mediated by the internet, from online communication platforms, in which it´s possible to establish social interactions with multiple actors, recovering conversation rooms, spaces of conviviality previously experienced in face-to-face interactions. They are, as we see in the approaches that stand out for their timeliness and because they are built from the Sociology of social medias, original. It´s an important example of the development of this increasingly relevant research agenda: the approach of human behaviors from the constitution of its reticular structure, but anchored from the mediation of the technology of virtual space. Keywords: Social Networks. Modernity. Sociability.